TINGKAT RESPON BERDASARKAN TAKSONOMI SOLO SISWA KELAS VIII YANG MENGALAMI MISKONSEPSI PADA TOPIK FAKTORISASI SUKU ALJABAR DI SMP NEGERI 5 KARANGANYAR PADA TAHUN PELAJARAN 2013/2014 - Fauzi Mulyatna; Imam Sujadi; Tri Atmojo Kusmayadi (Jurnal Pembelajaran Matematika, 2016)
Abstract: The objectives of this research were to identify and to describe about misconceptions, and to find out the levels of response of VIII grade students of SMP N 5 Karanganyar experiencing misconceptions about factorization of the tribe in algebra based on SOLO taxonomy. This research was categorized as a qualitative research using a case study design which was only focused on one selected and comprehended phenomenon deeply, and neglecting other phenomena. This particular phenomenon was the response level based on SOLO taxonomy of VIII grade students of SMP N 5 Karanganyar experiencing misconceptions about factorization of the tribe in algebra. The subject of this research were VIII grade students of SMP N 5 Karanganyar. The criteria to choose the main subject of the research were that the students had learnt a topic about factorization of the tribe in algebra and the main subject were taken based on test results by using CRI technique and the teacher’s recomendation. The data in this research were in the form of the students’ written answer results in finishing the problem solving test. The result of those written answers became the first data analysis of the researcher. Those first data analysis were in the form of description about misconceptions experienced by the subject and the levels of the subject’s response based on SOLO taxonomy in each problem. Those first data analysis were also used as a guide to do interviews. The interviews were both to clarify the subject’s written answers and to strengthen the data finding of the first data analysis. Then the results of the subject’s written answers and the results of the data analysis from the interview were drew conclusions. The triangulation technique was used as the validity of the data in the planning of the learning process by using problem solving test which was later clarified by the interview. The results of this research are follows. 1) The misconceptions experienced by the subject: the misconception in the use of the equal sign symbol (=), the subject were mistaken in interpreting the instruction order from left to right and the equals sign symbol (=) was wrongly interpreted as implication (⇒) to show the name which represented value and calculation with different results; the misconception of the substraction in algebra, it was a procedural misconception in the use of distributive rules by neglecting the minus sign; the misconception of the multiplication in algebra, it was a procedural misconception in the use of distributive rules by doing multiplication only in the first set when working with multiplication formula in algebra. 2) The levels of the subject’s response experiencing misconceptions were on the levels of multi-structural, uni-structural and pre-structural level.Keywords: Misconception, response level, SOLO taxonomy